2023
DOI: 10.1002/prp2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of sumatriptan revisited

Abstract: Scientific literature describes that sumatriptan is metabolized by oxidative deamination of its dimethylaminoethyl residue by monoamine oxidase A (MAO A) and not by cytochrome P450 (CYP)‐mediated demethylation, as is usual for such structural elements. Using recombinant human enzymes and HPLC‐MS analysis, we found that CYP enzymes may also be involved in the metabolism of sumatriptan. The CYP1A2, CYP2C19, and CYP2D6 isoforms converted this drug into N ‐desmethyl sumatriptan, which was fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…HumanP450Test1 comprised experimentally verified 65 CYP-substrate pairs and 15 CYP-nonsubstrate pairs described in the latest literature published between 2018 and 2023, and the CYPs in this data set refer to the nine categories of CYPs in the TrainSet. The distribution of Tanimoto Similarity coefficients for small molecules in HumanP450Test1 and the TrainSet is shown in Figure A. Both the t-SNE plot (Figure D) and the similarity distribution indicated that 58% molecules in HumanP450Test1 exhibited similarity values lower than 0.5, with no instances of similarity reaching 0.9 or higher.…”
Section: Resultsmentioning
confidence: 99%
“…HumanP450Test1 comprised experimentally verified 65 CYP-substrate pairs and 15 CYP-nonsubstrate pairs described in the latest literature published between 2018 and 2023, and the CYPs in this data set refer to the nine categories of CYPs in the TrainSet. The distribution of Tanimoto Similarity coefficients for small molecules in HumanP450Test1 and the TrainSet is shown in Figure A. Both the t-SNE plot (Figure D) and the similarity distribution indicated that 58% molecules in HumanP450Test1 exhibited similarity values lower than 0.5, with no instances of similarity reaching 0.9 or higher.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding free base Sumatriptan (Sum) like all triptans acts as a serotonin 5-HT 1B /5-HT 1D receptor agonist [2,3]. During its metabolism, Sum transforms into a glucuronide of indol-3-yl-acetic acid derivative via several steps [4]. The crystal structures of both Sum and HSum + •Hsucc − were published before [5,6].…”
Section: Introductionmentioning
confidence: 99%